Between Neutrality and Initiative: An Analysis of Indonesia's Foreign Policy in the Russia-Ukraine Conflict - Iswoyo Andrianto (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
.Resolution of the Russia-Ukraine Conflict and Analyzing Its Impact on Indonesia's National Interests. The theoretical framework used includes Joseph Nye's concept of Soft Power, which consists of three main elements: culture, political values, and foreign policy, as well as the Realism theory in international relations. The research methodology adopts a qualitative approach with a descriptive method. Data collection was carried out through literature review, observation, and in-depth interviews with key informants, namely the Head of Indonesia's Foreign Policy Strategy Agency and the Director of Europe II at the Ministry of Foreign Affairs. The research results show that Indonesia has taken several strategic steps in responding to the conflict, including acting as a mediator, pursuing diplomacy, urging a ceasefire, providing humanitarian aid, facilitating the evacuation of Indonesian citizens, and advocating for national security system reforms. The study also reveals that the Russia-Ukraine conflict significantly impacts Indonesia's national interests, including rising commodity prices, disruptions in global supply chains, economic uncertainty, export value fluctuations, and concerns over escalation toward World War III. These conditions drive Indonesia to be more active in international dialogue and diplomacy to prevent conflict escalation and achieve global peace.